A New Tool for Personalized Advertising in Shopping Malls: A Smart Billboard System - , Selay Ilgaz Sümer; , Çağatay Berke Erdaş; , Emre Sümer; , Ahmet Paker (Archives of Current Research International, 2022)
Along with the differences in customer preferences, a strong competition has emerged among the companies. Marketing managers have begun to design their marketing plans according to the target markets' needs and expectations. At this point, value-oriented marketing activities have become even more important. Personalized marketing is one of the most effective way of creating value to consumers. It is one of the best ways to establish relationships with target markets. Personalized marketing aims at delivering individualized messages to customers. By this means, personalized marketing activities attract more consumer attention relatively. It is a fact that it can also have positive impacts on the sales of the business. In this paper, a conceptual framework on personalized advertising is proposed. In this context, a hypothetical smart billboard system is designed at a shopping mall's entrance. The camera mounted system detects the car license plates via an image segmentation-based approach, which is composed of color space conversion, noise removal, edge analysis, geometric correction and connected component analysis. For license plate recognition, a 3-step image processing method, which comprises morphological dilation, character cropping and template matching is applied. A database is associating the detected license plates with the customers. When any match is found, the screen shows relevant advertisement to the customer. The study's major contribution is to propose a smart billboard system for shopping malls that presents personalized advertisements to customers based on their previous shopping experiences.